Executive orders - Clancy, Tom (HarperCollins London, 1998)
Jack Ryan, who had only accepted the Vice Presidency as a caretaker for a year suddenly finds himself President of the United States, and must contend with international enemies on both a personal and state level who see a U.S. internal crisis as a great opportunity